The Linkages between Mindfulness and Social Information Processing Theory on the Usage of Whatsapp Media Groups - Vusparatih, Dina Sekar (Humaniora, 2018)
The objective of the research was to find the linkages between mindfulness and social information processing theory on the use of WhatsApp group of Elementary school Principals in District Cilandak Region III for the distribution of various information and instructions. Through the concept of mindfulness and Social Information Processing theory approach (SIP), this research would explore the causes of the frequent emergence of noise, misunderstanding, and even tangency to the WA group that was carried on the meeting of headmaster meetings and relationships between members. The research problem was why WA group still causing issues among the Principals. By using the qualitative approach, data collection techniques used in this research were the interview, observation, and literature study. It is found that technological sophistication does not go parallel with maturity in communicating using media technologies. Lack of mindfulness in the WA group is a form of organizational communication that is simply transferred into the form of text communication on mobile phones that is being the main cause. Also, the organizational structure is still inherent in it and only serves as a bridge/form of interim communication because the main form of communication is still in the form of correspondence and face-to-face meetings.